A Vision for Development and Utilization of High-Throughput Phenotyping and Big Data Analytics in Livestock - Koltes, James E.; Cole, John B.; Clemmens, Roxanne; Dilger, Ryan N.; Kramer, Luke M.; Lunney, Joan K.; McCue, Molly E.; McKay, Stephanie D.; Mateescu, Raluca G.; Murdoch, Brenda M.; Reuter, Ryan; Rexroad, Caird E.; et al. (Frontiers in Genetics, 2019)
Automated high-throughput phenotyping with sensors, imaging, and other on-farm technologies has resulted in a flood of data that are largely under-utilized. Drastic cost reductions in sequencing and other omics technology have also facilitated the ability for deep phenotyping of livestock at the molecular level. These advances have brought the animal sciences to a cross-roads in data science where increased training is needed to manage, record, and analyze data to generate knowledge and advances in agriscience related disciplines. This paper describes the opportunities and challenges in using high-throughput phenotyping, “big data,” analytics, and related technologies in the livestock industry based on discussions at the Livestock High-Throughput Phenotyping and Big Data Analytics meeting, held in November 2017 (see: https://www.animalgenome.org/bioinfo/community/workshops/2017/). Critical needs for investments in infrastructure for people (e.g. “big data” training), data (e.g. data transfer, management and analytics), and technology (e.g. development of low cost sensors) were defined by this group. Though some subgroups of animal science have extensive experience in predictive modeling, cross-training in computer science, statistics and related disciplines are needed to use big data for diverse applications in the field. Extensive opportunities exist for public and private entities to harness big data to develop valuable research knowledge and products to the benefit of society under the increased demands for food of a rapidly growing population.